PENGARUH KONSENTRASI KATALIS TERHADAP RENDEMEN DAN KARAKTERISTIK FURFURAL DARI SABUT KELAPA: The Effect Of Catalyst Concentration on The Yield and Characteristics of Furfural from Coconut Husks - arziyah, dewi; Kasim, Anwar; Asben, Alfi; Busniah, Munzir (Universitas Andalas, 2025)
The use of coconuts produces agricultural waste such as coconut fiber. Immature coconut fiber and mature coconut fiber are lignocellulosic materials that can still be utilized, one of which is by processing them into furfural. Furfural is a clear liquid with a distinctive almond aroma that is widely used as an additive by the chemical industry. The purpose of this study was to determine the effect of the level of coconut fiber maturity with various catalyst concentrations and differences in reaction time on furfural yield. This study used two samples: mature coconut fiber and immature coconut fiber. The concentration variations used were 10%, 12%, and 14%. The time variations used were 20 and 30 minutes. From the results, it can be seen that the concentration, reaction time and type of raw material showed no significant effect on furfural yield. Young coconut fiber produced a higher yield than mature coconut fiber.